Learning and screening errors in an EPQ inventory model for supply chains with stochastic lead time demands. Issue 16 (18th August 2017) - Khan, Mehmood; Hussain, Matloub; Cárdenas-Barrón, Leopoldo Eduardo
Abstract : This paper investigates the role of variable lead time, learning in production and screening errors in a vendor–buyer supply chain with defective items. The vendor–buyer supply chain is modelled for supplying a single item considering that the lots from vendor may contain some defective items. It is assumed that demand during lead time follows a normal distribution. Moreover, the production time at vendor's facility is assumed to follow learning whereas buyer's screening for defective items is prone to errors as well. Numerical examples are presented to illustrate the impact of different variables in the model. The analysis shows that delay in transportation lead time forces the buyer to carry more inventories to avoid shortages. Further, Type I error has a major impact on this cost. It was found that learning in production keeps on reducing the total cost of the supply chain up to a threshold.